2023
DOI: 10.1001/jamainternmed.2023.1245
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease Exacerbations and Pneumonia Hospitalizations Among New Users of Combination Maintenance Inhalers

Abstract: ImportanceClinical guidelines on chronic obstructive pulmonary disease (COPD) recommend inhalers containing long-acting muscarinic antagonists (LAMAs) and long-acting β-agonists (LABAs) over inhalers containing inhaled corticosteroids (ICSs) and LABAs. However, data from randomized clinical trials comparing these combination inhalers (LAMA-LABAs vs ICS-LABAs) have been conflicting and raised concerns of generalizability.ObjectiveTo assess whether LAMA-LABA therapy is associated with reduced COPD exacerbations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…We conducted a cohort study using retrospective data from Optum's de‐identified Clinformatics® Datamart Database, commonly used for observational analyses 21–23 . Clinformatics includes national claims from commercial and Medicare Advantage plans from a single payer representing over 60 million unique persons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a cohort study using retrospective data from Optum's de‐identified Clinformatics® Datamart Database, commonly used for observational analyses 21–23 . Clinformatics includes national claims from commercial and Medicare Advantage plans from a single payer representing over 60 million unique persons.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a cohort study using retrospective data from Optum's de-identified Clinformatics ® Datamart Database, commonly used for observational analyses. [21][22][23] Clinformatics includes national claims from commercial and Medicare Advantage plans from a single payer representing over 60 million unique persons. The data includes information on demographic characteristics, enrollment status, inpatient and outpatient medical diagnoses (coded using ICD-10-CM and CPT-4) and prescriptions dispensed (National Drug Code number, quantity, and days' supply).…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…JAMA Internal Medicine publishes a wide range of articles, from those using weighting in surveys to produce nationally representative estimates, to methods such as regression discontinuity to address causal inference, to consideration of many forms of bias (including anchoring bias), and to the use of propensity score methods to balance potential confounding factors between exposed and unexposed groups . Understanding the statistical methods and concepts used in our publications will help clinicians interpret the literature, stay current, and make evidence-based informed decisions.…”
mentioning
confidence: 99%